Tourism Resources Development Policy in Increasing Regional Original Revenue in Bulukumba Regency - Syamsul Bahri, Andi Iqra; Usman, Jaelan; Fatmawati, Fatmawati (Borong Newinera Publisher, 2024)
Tourism as a core economy, is now a common goal, not only for all Kemenpar personnel, but also for the entire Indonesian nation. The research was conducted at the Bulukumba Regency Youth and Sports Tourism Office, this type of research is qualitative. This research data was obtained through observation, interviews, documentation, and media review. Data validity is done through tringulation of sources, techniques, and time and then analyzed through data reduction techniques, data presentation and conclusion drawing, and assisted by data analysis tools namely Nvivo 12 plus software. The results confirmed that tourism development in Bulukumba Regency has shown significant progress. The success of tourism development policy in the region can be measured by the effectiveness of communication in its implementation, where information is successfully delivered to all stakeholders with high consistency. The available resources have also been sufficient to cover various aspects, including human, financial, and material resources. However, there are shortcomings that still need attention, especially in the aspect of information resources, where there is still a need for improvement and provision of adequate information resources to support further tourism development.